Compressive Strength of Waste Utilized Concretes through Bio-mineralization Technique - I. Rohini; R. Padmapriya (Current Overview on Science and Technology Research Vol. 4, 2022)
Large quantities of concrete from building construction were produced, and demolitions accounted for 30-40% of total waste. Copper slag is produced in India at a rate of 6 to 6.5 tonnes per year out of a global total of approximately 33 tonnes. Approximately 2 million tonnes of e-waste are generated annually in India, where e-waste is emerging as serious public health and environmental concern. There will be a decline in the strength of concrete made from waste, necessitating the use of a different technique to enhance its properties. New technology known as "self-healing" concrete, which "heals" cracks on its own, points to a bright future for reducing the inevitable deterioration of concrete structures and the enormous maintenance expenses that go along with it. Nature, which encompasses us with a plethora of species endowed with exceptional capabilities, might serve as a source of inspiration for the development of novel regeneration strategies. Different civil and biotechnology experts have turned to microorganisms for the manufacture of ecologically sustainable, socially acceptable, and economically viable bio-building materials that can also offer high strength. This study examines the incorporation of waste materials into concrete and the determination of the compressive strength of waste-replaced concrete. Three major Wastes, including Demolition Wastes, Copper slag, and E-Wastes, were chosen to replace aggregate, and a spore-forming bacteria, Bacillus subtilis, was used as an admixture to improve the properties of concrete. Based on the obtained results, it has been determined that self-healing technology produces a significant and fruitful increase in mechanical properties.